Case Report: Living on the Edge—Transcatheter Mitral Valve Repair Related Infective Endocarditis - Lewandowski, Nicole; Berenjkoub, Ehssan; Gorr, Eduard; Horlitz, Marc; Boekstegers, Peter; Doss, Mirko; Sirat, Sami; Rottländer, Dennis (Frontiers in Cardiovascular Medicine, 2022)
Background: Infective endocarditis (IE) following mitral valve edge-to-edge repair is a rare complication with high mortality. Case Summary: A 91-year-old male patient was admitted to intensive care unit with sepsis due to urinary tract infection after insertion of a urinary catheter by the outpatient urologist. Two weeks ago, the patient was discharged from hospital after successful transcatheter edge-to-edge mitral valve repair (TEER) using a PASCAL Ace device. The initially withdrawn blood revealed repeatedly Proteus mirabilis bacteremia as causal for the sepsis due to urinary tract infection. An antibiotic regime with Ampicillin/Sulbactam was initiated and discontinued after 7 days. During the clinical course the patient again developed fever and blood cultures again revealed Proteus mirabilis. In transesophageal echocardiography (TOE), IE of the PASCAL Ace device was confirmed by a vegetation accompanied by a mild to moderate mitral regurgitation. While the patient was stable at this time and deemed not suitable for cardiac surgery, the endocarditis team made a decision towards a prolonged 6-week antibiotic regime with an antibiotic combination of Ampicillin 2g qds and Ciprofloxacin 750mg td. Due to posterior leaflet perforation severe mitral regurgitation developed while PASCAL Ace vegetations were significantly reduced by the antibiotic therapy. Therefore, the patient underwent successful endoscopic mitral valve replacement. Another four weeks of antibiotic treatment with Ampicillin 2g qds followed before the patient was discharged. Discussion: Proteus mirabilis is able to form biofilms, resulting in a high risk for endocarditis following transcatheter mitral valve repair especially when device endothelization is incomplete. Endoscopic mitral valve replacement could serve as a bailout strategy in refractory Clip-endocarditis.